[PP.27.02] PERFORMANCE OF FULLY AUTOMATED CHEMILUMINESCENCE ALDOSTERONE IMMUNOASSAY IN A POPULATION OF HYPERTENSIVE PATIENTS. (September 2017) - Pizzolo, F.; Zaltron, C.; Salvagno, G.; Lippi, G.; Caruso, B.; Zorzi, F.; Castagna, A.; Menguzzi, D.; Morandini, F.; Olivieri, O.
Abstract : Objective: Verify, retrospectively the ARR threshold in a population of hypertensive patients investigated for PA, and to attest the precision of the new method in intra venous salt loading (ivSLT) as confirmatory test. Design and method: We compared aldosterone results obtained with the CL method and RIA in stored blood samples from hypertensive patients investigated for PA (102 baseline and 85 after ivSLT). Results: A very good correlation between RIA and CL aldosterone assays was found in the all population for both aldosterone (r 0.922) and ARR (r 0.977). For the ARR, Deming regression demonstrated a good accordance between methods, and according to the fit model, considering our institutional cut-off of 32 pg/ml/pg/ml, the corresponding ARR cut off with CL aldosterone assay is 20 pg/ml/mUL. However, the correlation was was lower in the low end of aldosterone concentrations (r 0.676 for aldosterone <100 pg/ml by RIA). Accordingly, results of ivSLT with both assays were concordant in only 66% of patients. Conclusions: CL assay displays an accuracy similar to RIA for ARR screening, but its diagnostic accuracy remains suboptimal in the low end of aldosterone concentrations, which characterizes the setting of confirmatory tests such as ivSLT.